A survey on the awareness of interrelationship of periodontal disease and systemic health among Mahe population - Doraisamy Murugesan Hemalatha; Anil Melath; Mohammed Feroz; Kayakool Subair; Ashitha Mohandas; Nanditha Chandran (Wolters Kluwer Medknow Publications, 2020)
Background: Systemic health is the fundamental right of any individual, and it cannot be attained or maintained without oral health. Oral cavity is the gateway and the mirror of health. This link is often ignored. This lack of understanding of the correlation between oral and systemic health often leads to the poor systemic health because of the poor oral status. Aim: The aim of the study was to assess the awareness among the general public about periodontal diseases and its impact on systemic health. Materials and Methods: A questionnaire with 15 questions including general awareness about periodontitis and its impact on systemic health were given to patients and were asked to select their preferred option of yes, no, and don't know. The awareness of the individuals was categorized based on their educational qualification, age, and gender as well. Results: The results obtained showed increased awareness among females, postgraduates, and 35-50 years group of individuals according to their category of gender, education, and age group, respectively. Conclusion: There is always a strong influence of oral health on systemic well-being. This link among the two is often ignored and overlooked. Oral health upholds the overall well-being of the patient. Further studies need to be conducted on large scale population and camps need to be conducted to increase the awareness among the general public of periodontal diseases and their systemic impact.